Both of us : my life with Farrah - O'Neal, Ryan (Crown Archetype, 2012)
Ryan O'Neal and Farrah Fawcett. He was the handsome Academy Award--nominated star of Paper Moon and the classic romance Love Story. She was the beautiful, all-American Charlie's Angel, whose poster adorned the bedroom walls of teenage boys everywhere. One of the most storied love affairs in Hollywood history, their romance has captivated fans and media alike for more than three decades. In a tragic turn, the world lost Farrah after a tragic battle with cancer in 2009, but in his intimate memoir Ryan brings their relationship to vivid life.